2021
DOI: 10.3390/polym13234147
|View full text |Cite
|
Sign up to set email alerts
|

Manifest/Non-Manifest Drug Release Patterns from Polysaccharide Based Hydrogels—Case Study on Cyclodextrin—κ Carrageenan Crosslinked Hydrogels

Abstract: The aim of this study is to offer a comprehensive view on drug release from hydrogel, from both an experimental and a theoretical point of view. Aiming to benefit cyclodextrins’ properties (not irritant; stable; able to modify the physical, chemical and biological properties of active compounds; accessible at low prices) and those of carrageenan polysaccharide (antitumor, immunomodulatory, antihyperlipidemic, anticoagulant, biocompatibility, biodegradability), original hydrogel films based on beta cyclodextrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Previous studies showed that the theoretical models built on this hypothesis allowed insights concerning drug release at the microscopic level, which has been unaddressed thus far due to the complexity of the phenomena involved. For example, this revealed that, in the case of polymeric particles based on chitosan and gelatin, the trajectories of drug molecules follow cnoidal oscillation modes [25], while, for polysaccharide-based hydrogels, their trajectories evolved from a normal period doubling state towards damped oscillating via strong modulated dynamics [26].…”
Section: The Theoretical Model Of Drug Release In the Framework Of Scale Relativity Theorymentioning
confidence: 99%
“…Previous studies showed that the theoretical models built on this hypothesis allowed insights concerning drug release at the microscopic level, which has been unaddressed thus far due to the complexity of the phenomena involved. For example, this revealed that, in the case of polymeric particles based on chitosan and gelatin, the trajectories of drug molecules follow cnoidal oscillation modes [25], while, for polysaccharide-based hydrogels, their trajectories evolved from a normal period doubling state towards damped oscillating via strong modulated dynamics [26].…”
Section: The Theoretical Model Of Drug Release In the Framework Of Scale Relativity Theorymentioning
confidence: 99%
“…The use of Scale Relativity Theory (SRT) reduces this shortcoming by offering constants a and b physical significance. TRS implies that the entire drug release system, i.e., polymeric particle, drug, water, is considered a medium without interactions by equating the system complexity with fractality, for which the drug molecules are released on fractal curves, characterized by a fractal dimension D F as a measure of system nonlinearity and complexity [ 53 , 54 ]. In this theory, the Weibull equation is obtained as a short-time approximation of motion when convective processes are dominant [ 55 ], and the Weibull parameters can be defined as where n is the diffusion order, D is a structure coefficient that can be identified with the diffusion coefficient, L is a system characteristic length, and .…”
Section: Resultsmentioning
confidence: 99%
“…The nonlinearity and chaoticity of any polymer system are both structural and functional, and are determined by the interactions between its microscopic–macroscopic, local–global and individual–collective structural units. In such a framework situation, the universality of the dynamic laws of polymeric systems becomes natural and must be reflected in the mathematical procedures used [ 42 , 46 ]. There are authors who increasingly discuss the holographic implementation involved in the description of polymer dynamics (fractal paradigm of nature) [ 40 ].…”
Section: Discussion Of Differentiability To Nondifferentiability In D...mentioning
confidence: 99%
“…In the following, the tunnel effect is described through Scale Relativity Theory (SRT) [ 40 ] as a multifractal tunnel effect. SRT has been applied in describing the drug release from different types of delivery systems, including hydrogels [ 41 , 42 ], magnetic nanoparticles [ 43 , 44 ] and microparticles [ 45 , 46 ]. In this theory, the particles move on continuous but non-differential curves, named fractal curves.…”
Section: Drug Release Mimed As a Multifractal Tunnel Effectmentioning
confidence: 99%